Immunometabolic regulation during the presence of microorganisms and parasitoids in insects - Li, Shirong; Wang, Jing; Tian, Xing; Toufeeq, Shahzad; Huang, Wuren (Frontiers in Immunology, 2023)
Multicellular organisms live in environments containing diverse nutrients and a wide variety of microbial communities. On the one hand, the immune response of the organism can protect itself from the intrusion of exogenous microorganisms. On the other hand, the dynamic coordination of anabolism and catabolism in the organism is a necessary factor for the growth and reproduction of the organism and the population.Since the production of an immune response is an energy-intensive process, the activation of immune cells is accompanied by metabolic transformations that enable the rapid production of ATP and new biomolecules. In insects, the coordination of immunity and metabolism is the basis for insects to cope with environmental challenges and ensure normal growth, development and reproduction. During the activation of insect immune tissues by pathogenic microorganisms, not only can the utilization of organic resources be enhanced, but also the activated immune cells can usurp the nutrients of non-immune tissues by generating signals. At the same time, insects also have symbiotic bacteria in their body, which can affect insect physiology through immune-metabolic regulation. This paper reviews the research progress of insect immune-metabolism regulation from the perspective of insect tissues, such as fat body, gut and hemocytes. The effects of microorganisms (pathogenic bacteria/ nonpathogenic bacteria) and parasitoids on immune-metabolism was elaborated, which provided guidance for insect research and reference for research in mammals.